Co-producing Randomized Controlled Trials: How Do We Work Together? - Goldsmith, Lucy Pollyanna; Morshead, Rosaleen; McWilliam, Charlotte; Forbes, Gordon; Ussher, Michael; Simpson, Alan; Lucock, Mike; Gillard, Steve (Frontiers in Sociology, 2019)
In the light of the declaration ‘Nothing about us without us’ (Charlton, 1998), interest in co-production, and co-produced research is expanding. Good work has been done establishing principles for coproduction (Hickey et al., 2018) and for good quality involvement (4PI 2015; Involve, 2013) and describing how this works in practice in mental health research (Gillard, Turner and Neffgen, 2013, Gillard et al., 2012a, 2012b). In the published literature, co-production has worked well in qualitative research projects in which there is a high level of methodological flexibility. However, to change treatment guidelines in the UK, e.g. the National Institute for Health and Care Excellence guidelines, and influence commissioning (which determines the types of help Trusts offer people with mental health problems), high quality quantitative research is also needed. This type of research is characterised by formal methodological rules, which pose challenges for the scope of how coproduction can work in practice in quantitative projects. In this paper we describe the significant challenges and solutions we adopted to design and deliver a coproduced randomised controlled trial of mental health peer support. Given the low level of methodological flexibility of a randomised controlled trial, establishing clearly which methodological and practical decisions and processes can be co-produced, by whom, and how, has been vital to our ongoing coproduction as the project has progressed and the team has expanded. Creating and maintaining space for the supported dialogue, reflection and culture that coproduction requires has been vital. This paper aims to make our learning accessible to a wide audience of people developing coproduction of knowledge in this field.